Scenario Analysis of Rice Cultivation in Kerala - Hari, Athira; Kishore Kumar, N (Journal of Extension Education, 2017)
Rice is the staple food crop of Kerala. At present only 12% of the gross cropped area in the state is under paddy. The paddy fields in Kerala are constantly getting converted for other purposes. A steady decline in the area under rice cultivation occurred from 1980s onwards. This paper studies the changing trend in rice cultivation and provides the factors leading to shifting of rice cultivation.